Noninvasive Prenatal Test Results Indicative of Maternal Malignancies: A Nationwide Genetic and Clinical Follow-Up Study. Issue 22 (1st August 2022) - Heesterbeek, Catharina J.; Aukema, Sietse M.; Galjaard, Robert-Jan H.; Boon, Elles M.J.; Srebniak, Malgorzata I.; Bouman, Katelijne; Faas, Brigitte H.W.; Govaerts, Lutgarde C.P.; Hoffer, Mariëtte J.V.; den Hollander, Nicolette S.; Lichtenbelt, Klaske D.; van Maarle, Merel C.; et al.
Abstract : PURPOSE: Noninvasive prenatal testing (NIPT) for fetal aneuploidy screening using cell-free DNA derived from maternal plasma can incidentally raise suspicion for cancer. Diagnostic routing after malignancy suspicious–NIPT faces many challenges. Here, we detail malignancy suspicious–NIPT cases, and describe the clinical characteristics, chromosomal aberrations, and diagnostic routing of the patients with a confirmed malignancy. Clinical lessons can be learned from our experience. METHODS: Patients with NIPT results indicative of a malignancy referred for tumor screening between April 2017 and April 2020 were retrospectively included from a Dutch nationwide NIPT implementation study, TRIDENT-2. NIPT profiles from patients with confirmed malignancies were reviewed, and the pattern of chromosomal aberrations related to tumor type was analyzed. We evaluated the diagnostic contribution of clinical and genetic examinations. RESULTS: Malignancy suspicious–NIPT results were reported in 0.03% after genome-wide NIPT, and malignancies confirmed in 16 patients (16/48, 33.3%). Multiple chromosomal aberrations were seen in 23 of 48 patients with genome-wide NIPT, and a malignancy was confirmed in 16 patients (16/23, 69.6%). After targeted NIPT, 0.005% malignancy suspicious–NIPT results were reported, in 2/3 patients a malignancy was confirmed. Different tumor types and stages were diagnosed, predominantly hematologic malignancies (12/18). NIPT data showed recurrent gains and losses in primary mediastinal B-cell lymphomas and classic Hodgkin lymphomas. Magnetic resonance imaging and computed tomography were most informative in diagnosing the malignancy. CONCLUSION: In 231, 896 pregnant women, a low percentage (0.02%) of NIPT results were assessed as indicative of a maternal malignancy. However, when multiple chromosomal aberrations were found, the risk of a confirmed malignancy was considerably high. Referral for extensive oncologic examination is recommended, and may be guided by tumor-specific hallmarks in the NIPT profile.